The Importance of Continuing Higher Education to Face the Era of Society 5.0 and Industry 4.0: - - Sihombing, Dame Ifa; Lingga, Fitri Anjelita; Siregar, Aseantri Cian Br; Sianturi, Fitri Kristiani; Pasaribu , Mei Sartika (Jurnal Pengabdian Masyarakat Bestari, 2024)
Higher education plays a very important role in individual development and the progress of society as a whole. Participating in community service is one type of educational effort that gives students a taste of life outside of campus. SMA Negeri 1 Bandar Khalipah carries out community service with the aim of raising students' awareness and desire to pursue higher education in order to prepare them to face the increasingly complex era of industry 4.0 and society 5.0. Two questionnaires totaling 136 student responses were used to collect data for this study. The first questionnaire asks about the parents' level of education (X), while the second questionnaire contains 20 items that measure students' interest in continuing their education after high school (Y).